Comparison of PRE and POST COVID-19 Pandemic burn statistics: Initial experience from Rawalian Burn Center, Holy Family Hospital, RMU, Rawalpindi, Pakistan - Uzma Ali Kant, Maria Zubair, Fuad A K Niazi, Qamar Farooq, Sumra Munir, Seher Umer (Journal of Rawalpindi Medical College, 2021)
Objectives: To determine the change in the trend of burn patient epidemiology after the COVID-19 pandemic in terms of frequency of burn injury and mortality rate. Material and Methods: This cross-sectional descriptive study was carried out at Rawalian burn center, Plastic Surgery Department, Holy Family Hospital RMU Rawalpindi from 1st March to 31st July over a period of 05 months. All burn patients reporting to the Rawalian burn center during the specified period were included in this study by consecutive sampling. Patients were mainly admitted from emergency and some from OPD following the standard admission, inclusion, and exclusion criteria Results: Mean age of patients in the pre-COVID (Control) period March to July 2019 was 28.84 years with an SD of ±3.73. There were 63% females and 37% males. The total burn surface area range was 8-65% during this period. Whereas in the post-COVID period, March to July 2020 mean age of patients was 29.13 years with an SD of ±4.06. There were 60% females and 40% males. Whereas the total burn surface area range was 10-61% during this period. Frequency per month of burn injury progressively reduced to 58 patients and mortality rate to 1 in July 2020 (post-COVID period). The overall frequency of burn injury (n) during the control period was 367 patients whereas in the post-COVID period is reduced to 326 patients. So there was an 11.17% reduction as compared to the control period. A Chi-square test was applied and was found significant. Conclusion: Based on the current study it can be concluded that there is a progressive fall in frequency of burn injury and mortality rate during the ongoing COVID-19 pandemic as compared to the PRE-COVID period however further studies are needed to explore the cause of this falling trend.